The hidden glossaries of the Costa Rican literatura: bibliography contribution and creation of a search platform - Sánchez Mora, Alexánder (2018)
In this article, we study a minor lexicographic genre that has received little attention so far: the hidden glossaries in Costa Rican literary texts. From a wide corpus of glossaries, covering more than a century of Costa Rican literary history, a catalog is proposed that includes its typology, location and description. In addition, the glossaries typed were included in a Solr search engine, which allows for an agile and exhaustive consultation.